Respiratory Virus Vaccines: Pathways to Recommendations and Enhanced Coverage for At-Risk Populations - Stefania Maggi; Odile Launay; Rachel Dawson (Infectious Diseases and Therapy)
Abstract While marked differences exist between influenza virus, respiratory syncytial virus (RSV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), there is substantial overlap in the vulnerability of populations most at risk for severe disease following infection, chief among them being advanced age, multiple comorbidities, and immunocompromise. Vaccination is an established and effective preventative strategy to protect against respiratory viral infections (RVIs), reducing morbidity and mortality, minimizing the potential for long-term complications, and mitigating exacerbation of existing health conditions. Despite the demonstrated benefits of immunization throughout the life course and recommendations by health authorities, coverage rates of at-risk populations against vaccine-preventable diseases remain suboptimal and vary considerably by country and demographic strata. The objective of this supplement’s concluding article is to discuss the current barriers to vaccination and strategies to enhance coverage against RVIs among adult at-risk populations. Identified barriers include low awareness of the risks of vaccine-preventable diseases, low perceived benefits of vaccination, and doubts regarding vaccine safety, which together contribute to vaccine hesitancy. Additionally, logistical issues related to vaccine supply, access, and costs present further challenges in achieving optimal coverage. Potential strategies to overcome these barriers and improve uptake include strengthening and harmonizing immunization guidelines and improving respiratory disease surveillance systems to appropriately identify needs and direct resources. Co-administration or use of combination vaccines against multiple viruses may be a viable strategy to enhance coverage by simplifying schedules and improving access, together with future utilization of enhanced vaccine platforms to develop novel vaccines. In addition, vaccination-focused healthcare provider training and consumer education are recommended to address vaccine hesitancy. Reaching vaccination targets and expanding coverage in adult at-risk populations are increasingly achievable with the availability of new and updated vaccination strategies for respiratory viruses, but will require collective efforts across providers, policymakers, scientists, health officials, and the general population.